Budaya dan Penyakit Tidak Menular: Faktor Penentu Hipertensi di Desa Tenganan Pegringsingan, Karangasem, Bali - M. Farid (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Non-communicable diseases (NCDs) contribute to approximately 74 percent of global deaths, with cardiovascular diseases related to hypertension being the most significant, accounting for 17.9 million deaths each year. In Bali, the prevalence of hypertension has shown a steady increase, reaching 47.7 percent in Karangasem Regency. Existing epidemiological approaches remain insufficient as they focus predominantly on biological and behavioral determinants while overlooking cultural factors that influence health behaviors. This study aims to explore how shared knowledge within the Tenganan Pegringsingan community shapes and reinforces cultural practices that increase the risk of hypertension. Using a qualitative method with an ethnographic approach, data were collected through in-depth interviews and participant observation involving village officials, community elders, leaders of social drinking groups known as sekehe, and individuals participating in metuakan rituals. The findings demonstrate that the interaction between environmental, biological, and cultural factors sustains the practice of metuakan, a communal activity involving the consumption of palm wine (tuak), which is deeply embedded in local religious and social rituals. Long-term alcohol exposure through these practices influences biological processes and psychosocial conditions that affect heart rate and blood pressure. The study concludes that culturally embedded behaviors must be considered in the development of effective hypertension prevention strategies that are contextually grounded in local knowledge and practice.